Outcomes of a randomized controlled trial of neuromuscular training with real-time biofeedback in young female athletes - Kevin R. Ford; Jeffrey B. Taylor; Audrey E. Westbrook; Mark V. Paterno; Bin Huang; Anh-Dung Nguyen (BMC Musculoskeletal Disorders)
Abstract Background A large body of scientific work has been focused on reducing the high incidence rate of anterior cruciate ligament (ACL) injuries in young female compared to male soccer players. The purpose of this study was to determine the effects of a randomized clinical trial to reduce a risk factor of ACL injuries, knee abduction moment (KAM), with neuromuscular training and biomechanical biofeedback in adolescent female athletes. Methods A prospective, randomized, active comparator, open blinded, end-point trial was conducted with 150 (age: 13.3 ± 2.2 yrs, height: 156.1 ± 1 0.6 cm, mass: 50.2 ± 11.3 kg) female soccer players. Each participant received neuromuscular training and randomized into one of three arms: 1) an active control, considered sham biofeedback (NMT), 2) a knee-focused biofeedback group (NMT + K), and 3) a hip-focused biofeedback group (NMT + H). The participants completed two assessments: a baseline session prior to the intervention and a post-intervention session. The primary outcome measure was change knee abduction moment during a double leg drop vertical jump (DVJ). Additionally, an unplanned single leg cutting task was also recorded. As an exploratory outcome measure, athletic exposures and ACL injuries were recorded weekly for six months following the post-test session. Results A statistically significant reduction in KAM, during the DVJ, was found in all three intervention groups from baseline to the post-test (p < 0.05). However, statistically significant improvements in KAM during cutting was only observed in the NMT + H intervention group (p < 0.05). ACL injuries were not reported in any intervention group during the six months of follow up. Conclusions While female soccer players involved in neuromuscular training programs regardless of intervention group exhibit significant improvements in KAM during a double leg landing, those that engage in hip-focused biofeedback compared to knee-focused or sham biofeedback exhibit decreased KAM during an unanticipated cutting maneuver. Trial registration The Institutional Review Board at High Point University approved the study protocol. The clinical trial was registered at Clinicaltrials.gov (Identifier: NCT02754700) on 28/04/2016..